2023
DOI: 10.1097/01.ogx.0000912568.67045.6f
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vaccination and Risk of Hospitalization for Covid-19 Among Infants

Abstract: (Abstracted from N Engl J Med 2022;387:109–119)COVID-19 during pregnancy is associated with a greater risk of adverse pregnancy outcomes and neonatal complications. Studies have shown that mRNA vaccines are highly effective in preventing severe COVID-19 during pregnancy, and the Centers for Disease Control and Prevention recommends vaccination, including boosters, for people who are pregnant or plan to be pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…1). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Of the 15 studies, 2 case-control studies and 13 cohort studies reported on 90443 vaccinated pregnant women and 265063 unvaccinated pregnant women. The included studies reported data from six countries: Israel, UK, Romania, Canada, US, Sweden, and Norway (Table 1).…”
Section: Search Results and Basic Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Of the 15 studies, 2 case-control studies and 13 cohort studies reported on 90443 vaccinated pregnant women and 265063 unvaccinated pregnant women. The included studies reported data from six countries: Israel, UK, Romania, Canada, US, Sweden, and Norway (Table 1).…”
Section: Search Results and Basic Characteristicsmentioning
confidence: 99%
“…Recently, several studies about neonatal and early infant outcomes after maternal COVID-19 vaccination have already received increasing attention. [12][13][14][15][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, a comprehensive meta-analysis of neonatal outcomes after maternal COVID-19 vaccination is still lacking. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations